Korean Myth and Folklore on Game Character Design - Toha, I F; Ekawardhani, Y A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study dissected the visual aspect contained in Character design of Ahri’s Champion in League of Legends game with her classic skin to find the perception framing that transform nine tailed fox imagery from Korean myth and tales. League of Legends is a game that offers player an arena to fight, survive and win the game. This studies on Ahri’s character, which designed from Gumiho myth and tales, the concept that can intrigue curiosity and addiction from players. The study is a qualitative research by describing Ahri’s character based on it’s narration and other story about nine tailed fox, then dissect the character based on Manga-matrix principle that dissect character by it’s form matrix, costume matrix and personality matrix, analysis on similarity or relations among the theories as well as element that formed perception, and interpretation to the character. lastly design theory about ideology and culture that implemented on character design. The analysis shows that Ahri’s skin contains imagery framing that each element formed a new perception of nine tailed fox image. The costume is focused on featuring her charm and the color mostly white and red show that champion Ahri characteristic is not dark and evil but innocent and passionate. Ahri’s character design is an evidence that Gumiho image has shifted from symbols of evilness caused by people paradigm and the changes of social value in society